Smart Cities for Sustainable Development in India: Opportunities and Challenges - Daptardar, Vaidehi; Gore, Manasi (European Journal of Sustainable Development, 2019)
The concept of Sustainable development underlines the long lasting development of an economy by an efficient resource use fulfilling the economic, social and environmental aspects together. The SDGs by the UNDP focus on 17 goals for all countries to end poverty, protect the planet and ensure that all people enjoy peace and prosperity. The mission of Smart Cities in India is to promote cities that provide core infrastructure and give a decent quality of life to its citizens, a clean and sustainable environment and application of ‘Smart’ Solutions. The focus is on sustainable and inclusive development of the Mega cities, an indispensable outcome of the development process and urbanization implied in it. During the course of economic development over last 70 years in India, many cities have emerged as unsustainable and highly vulnerable to manmade calamities. This paper would elaborate on the details of Smart city project in India in the light of Sustainable development. The Smart cities mission though aims at sustainable development, this path is full of challenges along with some opportunities in disguise. The paper would suggest some policy implications such as developing smart villages along with these smart cities to bridge the gap between the rural and urban India. Keywords: Smart city mission, Sustainable development, Smart villages, Sustainable Development Goals (SDGs)